An Unusual and Facile Synthetic Route to Alumoles. Issue 25 (23rd April 2020) - Li, Jiancheng; Wu, Peng; Jiang, Wenjun; Li, Bin; Wang, Binju; Zhu, Hongping; Roesky, Herbert W.
Abstract: Reaction of the aluminum dialkynyl LAl(CCR)2 (L=N, N‐chelate ligand and R=organic group) with B(C6 F5 )3 proceeds through an intermediate with Al⋅⋅⋅η 2 ‐C≡C side‐on coordination to form the alumoles (2, 4, 6 ). A distinctive reaction pattern indicates a new facile synthetic route to aluminum‐containing heterocycles. The synthetic process is described, and the characterization of compounds and computational calculations were carried out. Furthermore, alumoles 2 and 4 exhibit an aggregation‐induced emission (AIE) of the bright yellow fluorescence. Abstract : Al in : Reaction of the aluminum dialkynyl with B(C6 F5 )3 proceeds through an intermediate with Al⋅⋅⋅η 2 ‐C≡C side‐on coordination to form the alumole. Some of the alumoles synthesized in this way exhibit an aggregation‐induced emission (AIE) bright yellow fluorescence.